Inclusive approaches in energy transition mainstreaming GEDSI for ecological justice - Nugraha, Ade (Journal of Critical Ecology, 2026)
Background: Environmental management in Indonesia is currently facing complex challenges arising from dependence on fossil fuels, the impacts of climate change, and persistent social inequalities experienced by vulnerable groups. This study aims to evaluate the extent to which environmental values can be integrated into community empowerment programs in the environmental sector, with a particular focus on the context of a just energy transition. Methods: This study employs a descriptive qualitative design using statutory and conceptual approaches to examine inclusivity in Indonesia’s energy transition, drawing on interviews, policy and legal document analysis, and secondary literature, with data analyzed through manual thematic coding, deductive reasoning, and triangulation to ensure credibility while acknowledging limitations in scope, legal coverage, and data availability. Findings: The findings indicate that although national and local policies have begun to emphasize inclusivity and community-based approaches, their implementation faces persistent structural barriers. These barriers include institutional limitations, insufficient inter-agency coordination, and restricted access to capacity-building resources especially for persons with disabilities who often encounter physical, technical, and informational obstacles in participating fully in environmental programs. Moreover, current policy frameworks still lack strong mechanisms to ensure meaningful involvement from marginalized groups rather than symbolic participation. Conclusion: This research highlights that the integration of gender equality, disability inclusion, and broader social inclusivity is not merely an additional component but a fundamental prerequisite for achieving fair community empowerment and sustainable environmental development. Novelty/Originality of this study: This research highlights that the integration of gender equality, disability inclusion, and broader social inclusivity is not merely an additional component but a fundamental prerequisite for achieving fair community empowerment and sustainable environmental development.